L’habitat rural des vallées de la Baïse et du Lot : contexte agraire et paysager - Hélène Mousset (In Situ)
An heritage survey has been undertaken for seventeen rural districts along the Lot river and the Baïse river. This area covers several geographical sections and can be characterized by a diversified dwelling pattern. The study of the connections between dwelling and agricultural outbuildings allows us to address the question of the agrarian systems and their evolution. Moreover, all the buildings of the area having been considered, this survey enables us to draw up an historical outline of the rural landscapes.